Halloween night murder - Meier, Leslie; Hollis, Lee; Ireland, Liz (Kensington Publishing Corp., 2025)
"In this trio of Halloween-themed novellas, a reporter in Maine investigates a teen's mysterious death, a group of friends shelters in a spooky farmhouse during a storm, and Mrs. Claus untangles magical mischief in Christmastown when Halloween chaos strikes"--